Factors associated with fertility rebound in the former Soviet Union: case study of Armenia and Tajikistan - Chung Gum Choe (2022)
While countries around the world have experienced a continuous decrease in fertility, in the early part of the new millennium (2005-15), almost all countries of the former Soviet Union recorded a fertility increase. Those countries had experienced a decrease in fertility after the dissolution of the Soviet Union in the 1990s, and the assumption was that economic recovery after the transition period led to a fertility rebound. In particular, a higher socioeconomic condition of the household and women’s status were possible contributing factors. The investigation of factors behind the fertility rebound in this region will help policymakers in the countries with similar contexts to address demographic dynamics. Armenia recorded an increase of its total fertility rate (TFR) from 1.65 to 1.76, while Tajikistan recorded a stable TFR at 3.61 during 2000-15. Data from the 2015-16 Armenia Demographic and Health Survey (DHS) and the 2017 Tajikistan DHS were used to examine factors associated with fertility in these two countries. Contrary to the hypothesis of this study, we found that age, marriage, and the desire for more children were positively related to Children Ever Born (CEB), while being employed, having higher education, and living in a household with a better-off wealth index were negatively related to CEB in both countries. Moreover, we found that the desired number of children among women was higher than the actual fertility in both countries, implying that unmet fertility goals may be considered as a potential driver for pro-natalist policies in the lowfertility countries.